STUDI RESEPSI KHALAYAK DALAM AKUN YOUTUBE â€œJEDA NULISâ€ HABIB JAâ€™FAR HUSAIN TENTANG FENOMENA CITAYAM FASHION WEEK - Hidayat, Aufa Maulana; Murniati, Murniati (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2024)
Citayam Fashion Week went viral in 2022, with the viral Citayam Fashion Week, many public figures came there. One of them is Habib Ja'far Husain. Habib Ja'far Husain is known as a millennial preacher, because he uses YouTube as a medium for preaching. With da'wah on YouTube, one of the audience's responses is through comments on YouTube. These comments or responses are considered important to be examined because to find out how effective Habib Ja'far Husain's da'wah was in using the media. This study aims to find out and analyze audience reception on Habib Ja'far Husain's